The research & practice of the on line monitoring methods for the capacitance to ground & grounding fault resistance of the networks - Xiao-Li Niu (7th IET International Conference on Advances in Power System Control, Operation and Management (APSCOM 2006), 2006)
Measuring of the single phase grounding fault resistance is a main subject in the fault management of the neutral non-effectively earthed system. And for the measuring of the grounding fault resistance, the important sector is the measuring of the capacitance to ground. Though there are some measures currently use but their accuracy are rather low. In this paper, we introduced two new different methods for measuring the capacitance to ground of the networks. Fornon-grounding neutral system and neutral compensating system. And on such base the grounding fault resistance can be finally calculated. (5 pages)